2021
DOI: 10.1111/nph.17880
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity, pleiotropy and fitness trade‐offs in Arabidopsis genotypes with different telomere lengths

Abstract: Telomere length has been implicated in the organismal response to stress, but the underlying mechanisms are unknown. Here we examine the impact of telomere length changes on Arabidopsis thaliana responses to three contrasting abiotic environments, and measure 31 fitness, development, physiology and leaf-level anatomy traits. We report that telomere length in wild type and short telomere mutants is resistant to abiotic stress, while elongated telomeres in ku70 mutants are more plastic. We also detect significan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…Computational analysis revealed that certain arabidopsis and maize accessions, and temperate-adapted rice were found to have longer telomeres associated with faster development and earlier flowering than other cultivars (Choi et al ., 2021). Recently Arabidopsis Col-0 was modified experimentally to possess degrees of longer and shorter telomeres than wild type; telomere length had a proportional effect on plant reproductive and anatomical traits (Campitelli et al ., 2022). Shorter telomeres in Col-0 resulted in increased seed output at native growing conditions, while longer telomeres in Col-0 appeared to provide reproductive and fertility advantages under certain environmental stressors, with longer time until first flower (Campitelli et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Computational analysis revealed that certain arabidopsis and maize accessions, and temperate-adapted rice were found to have longer telomeres associated with faster development and earlier flowering than other cultivars (Choi et al ., 2021). Recently Arabidopsis Col-0 was modified experimentally to possess degrees of longer and shorter telomeres than wild type; telomere length had a proportional effect on plant reproductive and anatomical traits (Campitelli et al ., 2022). Shorter telomeres in Col-0 resulted in increased seed output at native growing conditions, while longer telomeres in Col-0 appeared to provide reproductive and fertility advantages under certain environmental stressors, with longer time until first flower (Campitelli et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is variability among telomere lengths across different accessions within a species, while length is conserved within an accession (Shakirov and Shippen, 2004;Brown et al, 2011;Fulcher et al, 2015;Choi et al, 2021). Telomere length in plants has been associated with life history traits including seasonal and phenotypic variation, environmental interactions, sex, flowering time, and seed quantity (Liu et al, 2007;Mu et al, 2014;Choi et al, 2021;Osnato, 2021;Campitelli et al, 2022). Recent work in arabidopsis showed a number of associations between the telomere length and environmental response, with effects on phenotype (number of stomata, osmotic potential, leaf hydration), seed production, and overall reproductive fitness; phenotype variations were directly proportional to the telomere length divergence from the wild type Col-0 (Campitelli et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, we need to consider alternative models to explain telomere length variation for plants. Recently, links between telomere length and plant reproductive fitness and physiological traits have been discovered (Choi et al, 2021; Campitelli et al, 2022). Importantly, the studies have shown that variation in plant life‐history strategies can potentially influence the evolution of the telomere through natural selection.…”
Section: Why Do Telomere Lengths Vary In Plants?mentioning
confidence: 99%
“…Indeed, telomere length loss has been associated with exposure to extreme heat in dairy cattle (Seeker et al., 2021), increased river temperatures in fish (Debes et al., 2016) and developmental stress during embryogenesis in birds (Stier et al., 2020). While less is known about these relationships in plants, telomere length varies in response to aging and the environment in Arabidopsis , with impacts to fitness (Campitelli et al., 2022; Choi et al., 2021; Shakirov et al., 2022). Thus, telomeres may be a valuable biomarker for assessing response to environmental stress in plants.…”
Section: Introductionmentioning
confidence: 99%